Can respiratory physiology predict thermal niches?. Issue 1 (31st August 2015) - Verberk, Wilco C.E.P.; Bartolini, Fabrizio; Marshall, David J.; Pörtner, Hans‐O.; Terblanche, John S.; White, Craig R.; Giomi, Folco
Abstract : Predicting species responses to global warming is the holy grail of climate change science. As temperature directly affects physiological rates, it is clear that a mechanistic understanding of species vulnerability should be grounded in organismal physiology. Here, we review what respiratory physiology can offer the field of thermal ecology, showcasing different perspectives on how respiratory physiology can help explain thermal niches. In water, maintaining adequate oxygen delivery to fuel the higher metabolic rates under warming conditions can become the weakest link, setting thermal tolerance limits. This has repercussions for growth and scaling of metabolic rate. On land, water loss is more likely to become problematic as long as O2 delivery and pH balance can be maintained, potentially constraining species in their normal activity. Therefore, high temperatures need not be lethal, but can still affect the energy intake of an animal, with concomitant consequences for long‐term fitness. While respiratory challenges and adaptive responses are diverse, there are clear recurring elements such as oxygen uptake, CO2 excretion, and water homeostasis. We show that respiratory physiology has much to offer the field of thermal ecology and call for an integrative, multivariate view incorporating respiratory challenges, thermal responses, and energetic consequences. Fruitful areas for future research are highlighted.